Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


May be it is 4a^2- 9a^2- 2a -3b = 4a^2- 2a - 9b^2- 3b = 2a(2a- 1) - 3b(3b- 1) = (2a -1)(3b-1)(2a-1).
0 0 0
How can 2a (2a-1) -3b (3b-1)= (2a-1)(3b-1)(2a-1) ?
Sorry that`s wrong.How can i delete my answer.
The Brainliest Answer!
4a^2- 9b^2 -2a -3b
=(2a)^2 -(3b)^2 -(2a+3b)
=(2a+3b)(2a-3b) -(2a+3b)
1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts